Financial Feasibility Analysis for the Establishment of a Palm Oil Surfactant-Based Bio Oil Spill Dispersant (Bio-OSD) Plant - Irawan, Andre; Anas Miftah Fauzi; Erliza Hambali; Dwi Febriantini; Siska Pebriani (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
The industry plays a crucial role in the national economy, making significant contributions to GDP and employment. This study aims to analyze the financial feasibility of the Bio-OSD plant construction project, which produces bio oil spill dispersant from plant-based raw materials. The data used includes primary and secondary data collected from oil companies and the Surfactant and Bioenergy Research Center (SBRC) IPB over six months. The methods used in the analysis include Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B/C), Payback Period (PP), and Sensitivity Analysis. The analysis results show that the project has an NPV of Rp133,895,678,111, an IRR of 13.90%, a Net B/C of 2.34, and a PP of 5 years, 7 months, and 3 days, indicating that the project is feasible. Sensitivity analysis shows that the project remains viable despite a 10% increase in raw material and packaging costs, a 5% increase in fixed costs, and a 5% decrease in sales volume. The combination of these three variables results in an NPV of Rp54,189,090,981, an IRR of 5.64%, and a Net B/C of 1.54, with a PP of 7 years, 3 months, and 20 days. Therefore, the Bio-OSD plant is feasible to build despite facing changes in financial parameters